Form, force - Raúl Antelo (Universidad Nacional de Mar del Plata, 2021)
Literature, philosophy and art can either be seen as an aesthetical form or as distinct moments of the explosive force of life, a process of constant ‘becoming’. Antonio Candido conceives of literature as a social project but he is equally at home in textual analyses, in a sophisticated and unusual perspective. Paulo Emílio Salles Gomes, an ardent promoter and theorist of Brazilian cinema, always read it as a specific force for rupturing life: beyond everyday function, there is not a becoming for some preconceived end, but a becoming for the sake of change itself.